Transnational Influences in the Making of Indonesian’s First Qur’an: A Philological Study of the Mushaf Pusaka and its Egyptian-Turkish Lineage - Abidin, Zainal; Saeyd Rashed Hasan Chowdury (Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2024)
This article examines the influence of Egypt and Turkey on the Mushaf Pusaka of the Republic of Indonesia as the first state-issued Qur’an. This research is a qualitative study with a philological approach. The philological approach used does not aim to present the best edition of the edited text but rather to compare the text and writing style of the Mushaf Pusaka with previously written manuscripts. The results of the study show that the mushaf initiated by Abu Bakar Atjeh and Soekarno has similarities with two important mushafs in the Islamic world, namely the Mushaf Mesir published in 1924 and the Mushaf Bahriyyah from Turkey. Although during the writing of the Mushaf Pusaka (1948–1960), the majority of Indonesian Muslims still used the Mushaf Bombay, Salim Fachry, the author of the Mushaf Pusaka, did not refer to the Mushaf Bombay in his work. Instead, he used the 1924 Mushaf Mesir as the main reference in terms of text, such as rasm, qirā’āt, and ḍabṭ. Meanwhile, in terms of the number of pages and lines per page, the Mushaf Pusaka shows similarities with the Mushaf Bahriyyah from Turkey. Based on the results of data analysis, it can be concluded that the influence of Egypt and Turkey in the Mushaf Pusakaoccurred due to Salim Fachry’s educational background in Egypt and his mastery of the rules of calligraphy that were rapidly developing in Turkey.